Veracode: State of Software Security v11. Issue 2 (February 2021) - Unknown
Abstract : We all know that software contains flaws and that this is the major cause of security vulnerabilities. Veracode makes it its business to examine code for errors that could lead to disaster and its annual report often makes for uncomfortable reading. This year is no different.